Laparoscopic Appendectomy for Acute Appendicitis Complicated by Pancytopenia in Two Patients with Hematologic Diseases - Kojima, Keita (J Anus Rectum Colon, 2021)
A 25-year-old male (Case 1) was waiting for a bone marrow transplant for myelodysplastic syndrome. Due to acute appendicitis, he was advised to undergo gastroenterological surgery. After blood transfusion, he underwent an emergency laparoscopic appendectomy, as no blood cell recovery was expected. The postoperative course was uneventful, and he was discharged. A 71-year-old female (Case 2) developed acute appendicitis during chemotherapy for acute myeloid leukemia (AML). At the time of onset, since her myelosuppression was expected to improve in approximately 1 week, a conservative treatment was administered. However, due to the progression of AML, the expected blood cell recovery did not occur. Therefore, laparoscopic appendectomy was performed 25 days after onset. She was discharged without postoperative adverse events. In cases of acute appendicitis in patients with hematologic disease accompanied by pancytopenia, it is important to establish a careful treatment plan considering the possibility of recovery from myelosuppression and the need to control an intraperitoneal infection in conjunction with a hematologist. Laparoscopic surgery, which is minimally invasive, was an effective surgical procedure.